INTERAKSI SOSIAL SISWA PADA PENGGUNA MEDIA SOSIAL TIKTOK DI SMAN 111 JAKARTA - Fidela, Fakhira Alyaa; Nurmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the social interaction patterns of students who use TikTok as a social media platform at SMAN 111 Jakarta, examined through George Herbert Mead's theory of symbolic interactionism. The theory encompasses three primary dimensions: the interpretation of symbols (mind), the formation of self-concept (self), and the role of the social environment (society). This study employed a descriptive qualitative approach, with data collected through semi-structured in-depth interviews, non-participatory observation, and documentation. Six informants participated in this study, consisting of four Grade X students who actively use TikTok, one homeroom teacher, and one school counselor. The findings reveal three key results. First, students' symbol interpretation processes occur actively and reflectively, although the meaning-making of certain symbols on TikTok remains a challenge. Second, TikTok functions as a space for self-concept formation, where digital responses such as likes, comments, and follower counts influence students' self-confidence and social identity. Third, the digital social environment on TikTok shapes new norms and interaction patterns that carry over into school life, including the emergence of opinion leaders among students. This study affirms the relevance of symbolic interactionism theory in understanding adolescent social behavior in the digital age, and highlights the importance of developing comprehensive digital literacy within educational settings.